Advances in molecular basis of response to immunotherapy for penile cancer: better screening of responders - Xu, Da-Ming; Chen, Ling-Xiao; Zhuang, Xiao-Yu; Han, Hui; Mo, Miao (Frontiers in Oncology, 2024)
Penile cancer is a rare malignant tumor of the male urinary system. The treatment benefit of standard first-line chemotherapy is not ideal for patients with locally advanced or metastatic lymph nodes. Immunotherapy has brought new treatment strategies and opportunities for patients with penile cancer. At present, clinical studies on immunotherapy for penile cancer have been reported, and the results show that it is effective but not conclusive. With the development of immunotherapy and the progress of molecular research technology, we can better screen the immunotherapy response population and explore new combination treatment regimens to evaluate the best combination regimen and obtain the optimal treatment options, which is also an important research direction for the immunotherapy of penile cancer in the future.